Ingestion of mixed meals of low or high glycaemic index does not affect performance in 3.000m running - Almeida, K. S.; Sales, M. M.; Moreira, S. R.; de Moraes, J. F. V. N.; Asano, R. Y.; de Sousa, M. V.; de Souza, M. N. M.; Simoes, H. G.; Campbell, C. S. G. (Serbian Journal of Sports Sciences, 2012)
The purpose of this study was to analyze the effects of meals with high (HGI) and low glycaemic index (LGI), and fasting (FAST) on performance, blood glucose (GLU), blood lactate concentration ([LAC]) and expired gases before, during, and after a test of running 3.000m. Eleven males underwent three experimental sessions (HGI, LGI and FAST). [LAC] and GLU were collected in the postprandial (PP) and post-exercise period. Expired gases were collected during all procedures. There were no differences (p>0.05) in performance (VO2peak and mean velocity) during 3.000m running. GLU in the HGI session was lower immediately after the running test when compared to LGI and FAST.